Dynamic business process management in the knowledge economy : creating value from intellectual capital - Szelągowski, Marek (Lecture notes in networks and systems ;, 2019)
This book describes modern dynamic business process management (dynamic BPM), which is considerably different from traditional BPM from 20, 10, or even 5 years ago. It demonstrates why traditional BPM is not sufficient in the knowledge economy (KE), while also highlighting the opportunities provided by dynamic BPM - the form of management that practitioners and academics deal with on a daily basis. This involves mastering and implementing e.g. case management, process mining, and RPA, and integrating them with knowledge management. But more importantly, dynamic BPM makes full use of the dynamism of knowledge workers: the people who actually create innovative products and services tailored to the specific needs of clients. The book was primarily written for those managers who see advantageous opportunities amidst the ongoing changes. Accordingly, it focuses more on innovations emerging from practice than on theoretical, academic reflection. In addition to helping organizations operating in the KE to prepare for and implement process management, the book is intended as a source of inspiration for process management researchers and iBPMS system vendors.- Resumé vydavatel